Riparian Buffer Strips as a Multifunctional Management Tool in Agricultural Landscapes: Introduction - Stutter, Marc I.; Chardon, Wim J.; Kronvang, Brian (Journal of environmental quality, 2012)
Catchment riparian areas are considered key zones to target mitigation measures aimed at interrupting the movement of diffuse substances from agricultural land to surface waters. Hence, unfertilized buffer strips have become a widely studied and implemented “edge of field” mitigation measure assumed to provide an effective physical barrier against nitrogen (N), phosphorus (P), and sediment transfer. To ease the legislative process, these buffers are often narrow mandatory strips along streams and rivers, across different riparian soil water conditions, between bordering land uses of differing pollution burdens, and without prescribed buffer management. It would be easy to criticize such regulation for not providing the opportunity for riparian ecosystems to maximize their provision for a wider range of ecosystem goods and services. The scientific basis for judging the best course of action in designing and placing buffers to enhance their multifunctionality has slowly increased over the last five years. This collection of papers aims to add to this body of knowledge by giving examples of studies related to riparian buffer management and assessment throughout Europe. This introductory paper summarizes discussion sessions and 13 selected papers from a workshop held in Ballater, UK, highlighting research on riparian buffers brought together under the EU COST Action 869 knowledge exchange program. The themes addressed are (i) evidence of catchment‐ to national‐scale effectiveness, (ii) ecological functioning linking terrestrial and aquatic habitats, (iii) modeling tools for assessment of effectiveness and costs, and (iv) process understanding enabling management and manipulation to enhance pollutant retention in buffers. The combined understanding led us to consider four principle key questions to challenge buffer strip research and policy.